Illuminating the dark matter of social neuroscience: Considering the problem of social interaction from philosophical, psychological, and neuroscientific perspectives - Przyrembel, Marisa; Smallwood, Jonathan; Pauen, Michael; Singer, Tania (Frontiers in Human Neuroscience, 2012)
Successful human social interaction depends on our capacity to understand other people’s mental states and to anticipate how they will react to our actions. Despites its importance to the human condition, there are still quite a few debates about how we actually solve the problem of understanding other peoples’ actions, feelings and thoughts. Here we consider this problem from philosophical, psychological, and neuroscientific perspectives. In a critical review we show that attempts to draw parallels across these complementary levels of analysis are premature: The second-person perspective does not map directly to simulation theories, online social cognition or shared neural networks underlying action observation or empathy. Nor does the third-person perspective map onto theory-theory accounts of other agents mental states, offline social cognition or the neural networks that support Theory of Mind. We further propose that important qualities of social interaction emerge through the reciprocal interaction of two independent agents whose unpredictable behaviour requires a continual updating of models of their partner internal state. This analysis draws attention to the need for paradigms that allow two individuals to interact in a spontaneous and natural manner and to adapt their behaviour and cognitions in a response contingent fashion due to the unpredictability of their partners behaviour. Even if such paradigms were implemented, it is possible that the specific neural correlates supporting such reciprocal interaction would not reflect the processes unique to social interaction because much real social behaviour may reflect the use of basic cognitive and emotional process in a novel and unique manner. Given the role of social interaction in human evolution, ontogeny and every-day social life, a more theoretically and methodologically nuanced approach to the study of social interaction will help to shed new light on the dark matter of social neuroscience.